The remarkable dynamics in the establishment, rearrangement, and loss of dentition during the ontogeny of the sterlet sturgeon - Pospisilova, Anna; Stundl, Jan; Brejcha, Jindrich; Metscher, Brian D; Psenicka, Martin; Cerny, Robert; Soukup, Vladimír (Developmental dynamics, 2022)
BACKGROUND: Sturgeons belong to an early-branching lineage often used as a proxy of ancestor-like traits of ray-finned fishes. However, many features of this lineage, such as the transitory presence and the eventual loss of dentition, exemplify specializations that, in fact, provide important information on lineage-specific evolutionary dynamics. RESULTS: Here, we introduce a detailed overview of the dentition during the development of the sterlet sturgeon. The dentition is composed of tooth fields at oral, palatal, and anterior pharyngeal regions. Oral fields are single-rowed, non-renewed and are shed early. Palatal and pharyngeal fields are multi-rowed and renewed from the adjacent superficial epithelium without the presence of the successional dental lamina. The early loss of oral fields and subsequent establishment of palatal and pharyngeal fields leads to a translocation of the functional dentition from the front to the rear of the oropharyngeal cavity until the eventual loss of all teeth. CONCLUSIONS: Our survey shows the sterlet dentition as a dynamic organ system displaying differential composition at different time points in the lifetime of this fish. These dynamics represent a conspicuous feature of sturgeons, unparalleled among extant vertebrates, and appropriate to scrutinize developmental and evolutionary underpinnings of vertebrate odontogenesis.
Keywords: Animals; Dentition; biologická evoluce; Acipenser; Tooth; odontogeneze; Odontogenesis; Fishes; odontogenesis; ryby; dentice; zuby; teeth patterning; Vertebrates; tooth development; obratlovci; non-teleost fishes; zvířata; Biological Evolution